Penerapan Teknologi Pemasaran Digital Berbasis E-Commerce Pada Kelompok Sumberwangi Sentra Fish - As'ari, Hasyim; Qiram, Ikhwanul; Kurnia, Tristi Indah Dwi (Fakultas Teknik, Universitas PGRI Banyuwangi, 2024)
The community service activity conducted at the Sumberwangi Sentra Fish group in Jambewangi Sempu Banyuwangi aimed to address the marketing issues faced by the partner group. Additionally, the activity sought to measure interest and the usefulness of the developed platform to support the program's sustainability. The methods used in this community service included the development of an e-commerce platform, socialization, training, and mentoring. Evaluation of the activity was conducted using instruments in the form of questionnaires to assess interest, the usefulness of technological innovations, and the community service activities. The developed e-commerce platform effectively addressed the partner's marketing challenges. The platform is designed as a web-based application that can be easily accessed via smartphones or directly through the website https://sumberwangisentrafish.com/. The user interface (UI) of the e-commerce platform provides information about products, featuring easily understandable menus that include product displays and detailed information about each marketed item. The interface design focuses on operational ease. Results from the questionnaire indicated that out of 13 respondents, 85% expressed interest and stated that they found the technology and activities to be important, very understandable, and very easy to use, while 75% felt ready to implement digital marketing strategies. In conclusion, the community service demonstrated that the e-commerce platform can enhance the welfare of the partner group and has the potential to support business sustainability.